Exposure to misoprostol and hormones during pregnancy and risk of congenital anomalies Exposição ao misoprostol e hormônios durante a gravidez e risco de anomalia congênita - Tatiane da Silva Dal Pizzol; Maria Teresa Vieira Sanseverino; Sotero Serrate Mengue (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
This study evaluated the association between use of misoprostol and other drugs to induce menstruation, and congenital anomalies. A sample of 4,856 pregnant women 20 years and older were enrolled consecutively in prenatal services in the Unified National Health System, in six Brazilian State capitals. Data on socio-demographics and use of medicines were obtained using an interview from the 21st to 28th week of pregnancy. Other data, including information on delivery and diagnosis of congenital anomalies by the attending neonatal physician were obtained from patient charts. Potential confounders were adjusted by logistic regression. Use of drugs to induce menstruation was reported by 707 women (14.6%), of whom 120 (17%) reported use of misoprostol. After adjusting for the study center, a positive association was observed between misoprostol and congenital anomalies (OR = 2.64; 95%CI: 1.03-6.75); a positive association was also observed for sex hormones (OR = 2.24; 95%CI: 1.06-4.74). The results suggest that the use of misoprostol or sex hormones during pregnancy increases the risk of congenital anomalies. Este estudo avalia a associação do uso do misoprostol e de outros produtos utilizados para induzir a menstruação com anomalia congênita. Foram arroladas consecutivamente 4.856 mulheres com vinte anos de idade ou mais, procedentes de serviços de pré-natal do Sistema Único de Saúde em seis capitais brasileiras. Dados sócio-demográficos e o uso de medicamentos foram obtidos por meio de entrevista, entre a 21ª e a 28ª semanas de gestação. Outros dados, incluindo informações sobre o parto e o diagnóstico de anomalia congênita, realizado pelo médico que assistiu o recém-nascido, foram obtidos no prontuário. Potenciais confundidores foram ajustados por meio de regressão logística. O uso de produtos para induzir a menstruação foi relatado por 707 gestantes (14,6%), das quais 120 (17%) referiram-se ao misoprostol. Após ajustamento para o centro de realização da pesquisa, foi verificada uma associação positiva entre misoprostol e anomalias congênitas (RC = 2,64; IC95%: 1,03-6,75); para hormônios sexuais também foi verificada uma associação positiva (RC = 2,24; IC95%: 1,06-4,74). Os resultados sugerem que o uso de misoprostol ou hormônios sexuais durante a gravidez aumenta o risco de anomalia congênita.